The multifaceted role of long non-coding RNA DLEU1 in cancer progression: implications for diagnosis and therapy - Stanicki, Paweł; Szarpak, Julita; Pażyra, Aldona; Kusak, Natalia; Żak, Natalia; Jaworska, Barbara (Quality in Sport, 2024)
INTRODUCTION AND PURPOSE: Long non-coding RNAs are key regulators of gene expression and tumorigenesis. Deleted in leukemia 1 (DLEU1) is significant in cancer development. This article reviews DLEU1's role across cancers, assessing its diagnostic and therapeutic potential. METHODS: A review of scientific articles from PubMed and Google Scholar was conducted. DESCRIPTION OF THE STATE OF KNOWLEDGE: DLEU1 drives tumor growth in glioblastoma, esophageal, colorectal, and oral cancers by interacting with key miRNAs and genes, promoting malignancy. In breast and ovarian cancers, DLEU1 modulates migration and invasion via specific pathways. In cervical cancer, DLEU1 is linked to immune modulation and serves as a prognostic marker. SUMMARY: DLEU1 is a vital regulator in various cancers, offering potential as a diagnostic and therapeutic target.